Efficient Synthesis of Sulfinate Esters and Sulfinamides via Activated Esters of p-Toluenesulfinic Acid - Gafur, Sayed Habibul; Waggoner, Stephanie L.; Jacobsen, Eric; Hamaker, Christopher G.; Hitchcock, Shawn R. (Synthesis, 2018)
Sulfinate esters were prepared by the process of activating p-toluenesulfinic acid with either cyanuric chloride, methanesulfonyl chloride, or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC-HCl). Activation of p-toluenesulfinic acid with cyanuric chloride led to the formation of sulfinate esters that were accompanied by the formation of the corresponding sulfones. The use of methanesulfonyl chloride for activation via methanesulfonic p-toluenesulfinic anhydride afforded mixtures of sulfinate esters and methanesulfonates. The use of the carbodiimide EDC proved to yield the best results with the highly selective formation of the target sulfinate esters. The use of trimethylacetic p-toluenesulfinic anhydride or cyanuric chloride to achieve the synthesis of sulfinamides proved to be ineffective due to poor chemoselectivity of the nucleophilic attack on the activated p-toluenesulfinic acid anhydride. Ultimately, the use of EDC-HCl to form the sulfinamides proved to be the best pathway for synthesis.
Keywords: sulfinate ester; sulfinic acid; sulfinamide; cyanuric chloride; EDC; activated ester